PRE-SERVICE TEACHERS’ REFLECTIONS OF SOUTH AFRICAN SCIENCE CLASSROOMS - Singh, SK; Singh, RJ (South African Journal of Higher Education, 2016)
The introduction of outcomes-based education in South Africa placed many challenges on the transformation of science classrooms. The 2009 National Education Evaluation and Development Unit (NEEDU) Report concluded that South African rural and township schools are largely dysfunctional. This article examined some of the reasons for the ‘collapse’ of rural schools as seen through the eyes of pre-service science teachers. It explored the reflections of 30 pre-service teachers in science classrooms in the Limpopo Province of South Africa where the majority of schools lack infrastructure such as libraries, laboratories and computer rooms. The reflections of pre-service science revealed that the culture of teaching and learning has been negatively affected by lack of resources, poor training of science teachers, incompetent school management teams, overcrowding of science classrooms and a plethora of curriculum policies. Furthermore, teachers had not fully embraced all aspects of curriculum policy. This has resulted in the outcomes identified for science not being completely achieved. Pre-service teachers found it challenging to adapt to the ‘realities’ of teaching science without science equipment or appropriate resources. Suggestions made by pre-service teachers to improve science teaching in schools are considered in the recommendations of this article. Some of the recommendations are: development of resource packs for teachers in rural schools; a module on improvisation and innovation in science in pre-service and in-service training; establishing science nodal hubs or science resource centres in rural areas; improving awareness of science through competitions, open days and science clubs; developing mobile libraries and science laboratories for rural teachers; and establishing science committees in schools or regions.